ANALISIS STABILITAS DAN PEMILIHAN PERKUATAN LERENG PADA RUAS JALAN PEMUDA KM. 3 KABUPATEN KOLAKA PROVINSI SULAWESI TENGGARA - Yatjong, Isramyano; Fachryano, Fachryano (IST AKPRIND YOGYAKARTA, 2018)
Slope conditions have been excavated due to widening of the road from the toe to the top of the slope. High rainfall instensity causes erosion along the slope surface and circular landslide on the slope. Geotechnical investigation was conducted to obtain data of physical and mechanical properties of soil in landslide area. Slope geometry excavated based on field conditions.Slope stability is based on a safety factor of 1,3 using the Bishop limit equilibrium method via Sldie v.06 and finite element method through Phase2 v.08 software and provides slope reinforcement method.The result of slope stability analysis using Slide v.06 is the value of critical safety factor equal to 1,009 with the landslide area of the first bench and the second bench. While the results of the analysis using the Phase2 v.08 is the value of critical safety factor equal to 0,980 with the landslide area of the first bench and the second bench. Both critical safety factors indicate unstable before to slope reinforcement that is still below the permit SF of 1,30 so that reinforcement is required stone retaining wall, pipe installation on slope face, make a water trench, planting and maintain vegetation at the top of the slope.